Characteristics of carcasses and meat from feedlot lambs fed with sunflower cake - De Oliveira, Euclides Reuter; Monção, Flávio Pinto [UNESP]; De Araújo Gabriel, Andréa Maria; Fernandes, Alexandre Rodrigo Mendes; De Almeida Nascimento, Felipe [UNESP]; De Souza Abreu, Felipe; Do Valle Mendes Da Silva, Leandro; Da Silva, Loan Henrique Pereira (Universidade Estadual de Londrina, 2016)
The aim of the experiment was to evaluate the characteristics of the carcasses and meat of feedlot lambs that received diets supplemented with sunflower cake; correlations among the variables were also performed. The experimental design was a randomized block design with four treatments (sunflower cake added at 0, 10, 20, and 30% dry matter to the base diet) and seven replications per treatment. The diets were formulated with genotypes of Cynodon hay and corn- and soybean meal-based concentrate that were premixed at the ratio of 50:50 (hay:concentrate) and were fed to the lambs in two portions daily at 08:00 and 14:00. The feed conversion of the animals was adversely affected (P<0.05) by the increase in the feedlot period in the individual stalls. For each additional day of confinement, the feed conversion increased by 0.0096 kg DM/kg of weight gain. Based on the linear regression model for the average loin pH, one hour after slaughter, the pH was reduced by 0.04 units. The marginal change in pH between the longest and the shortest times after slaughter was 14.11%. The weights of the animals at slaughter were not significantly correlated with the carcass yields. Sunflower cake is a suitable dietary supplement for lambs in intensive production systems and can be a substitute for soybean meal at up to 20%.
Keywords: By-products; Feed conversion; pH; Sheep; Yield